Administración financiera aplicada a la importadora Ortega Cia. Ltda. en la ciudad Loja 2010 - 2011. - Ramírez Gualán, Laura Gabriela (2012)
This work called “ADMINISTRACION FINANCIERA APLICADA A LA IMPORTADORA ORTEGA CIA. LTDA., DE LA CIUDAD DE LOJA; PERIODO 2010-2011”is intended to raise awareness of the import to apply financial management tools, and so contribute to the financial department of the Importer to take the right decisions in the management economic resources efficiently. The trading company Importer Ortega is a limited company legally established in 1976, dedicated to the sale of construction products, which through the analysis of macroeconomic indicators such as inflation, GDP, foreign investment, business confidence index, among others, and based on the analysis of socio economic, political, governmental and technological, has identified the opportunities and threats that affect the normal operation of the importer. Also through an interview directed to Ms. Anna Poma internal diagnosis was made, which allowed to know the historical background of the company, the structure of the finance function, manual accounts receivable, accounting system, internal control, personnel selection , staff profile that integrates the financial department has detected that no knowledge of the various financial management procedures. Consequently by applying vertical analysis, applied to the balance sheet of the Importer Ortega determines that the item of greater weight on total assets is inventory with 56%, the account represents 41 suppliers, 41%, followed by assets Available with 17.59%, and the obligations to financial institutions 11.99% operating income comprise 99.86%, the cost of sales 88.81%, 8.89% expenses and net margin 1.12% of total income. Horizontal analysis indicates positive changes in current assets 55.17%, fixed assets 107% increase in financial obligations 44.93%, 43.16% payable benefits, obligations with the IRS 438.03% and decrease in equity in the 51.74%. Then by applying financial indicators determined the level of liquidity, debt, and profitability taking activity so the company has a working capital of $ 20,116.72, also has high levels of debt in relation to the assets of 86.75% reaching above the competition, the reasons for the slow activity indicate turnover of accounts receivable and inventories, profitability ratios indicate the performance of asset sales and equity 6.84% from 64.44%. Likewise, the classification of amounts indicate lower costs in terms of fixed costs $ 274,487.87 allowing leverage by 5.06% as per point to increase there will be more sensitive to the change in profits for the high values variable costs $ 4,228,383.58 causing the variation in operating income of 14.97% and the net margin of 21.51%. Moreover, the volume of sales needed where there will be no gain or loss is $ 3,921,255.29 it is high, the origins, funding applications indicate that the increased value of cash in operating activities of the company, the uses and sources of funds are equivalent $ 379,705.45 as the capital of $ 281,067.27 dollars. Based on the analysis of the above factors is evident ignorance of financial management techniques, excessive decrease in working capital and inventories portfolio turnover slow. This proposed solution was raised as it is the training of financial staff, settlement policy reform portfolio, adequate working capital management, planning future cash needs based on economic factors internal and external administrative determining the total cash inflows of $ $ and cash outflows obtaining the projected ending cash balance $ 89,835.58, plus pro forma statements are prepared to determine the situation and the financial performance of the importer Ortega.